TERJEMAHAN AL-QURAN KEMENAG 2018 DAN IMPLIKASI IDEOLOGI: ANALISIS TENTANG AYAT-AYAT JIHAD - Solihin Solihin; Aflatun Muchtar (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This thesis aims to reveal how the 2018 Ministry of Religion Al-Quran Translation and Ideological Implications: Analysis of the verses of Jihad. This study uses library research research methods. In its operation, this research is more on the study and assessment of the 2018 Ministry of Religion Al-Quran translation and Ideological Implications. This study aims to describe the implications of ideology.The research method of library research is to examine books related to existing problems and related to the problems discussed in this thesis. This study aims to describe the ideological implications that occurred in Indonesia before and after the publication of the 2018 Ministry of Religion's translation of the Al-Quran. And the typology of radical jihad is also different which has an excessive understanding of the meaning of jihad only as a form of war. This is, of course, different from the liberal typology of reducing the means that are not used as a tool of war should not be destroyed. Acts of terrorism in Indonesian society in the year prior to 2018 were very widespread because preventing acts of terrorism were dominantly only carried out by the government after 2018 until now the community's contribution was felt especially for the role of religious leaders who contributed to preventing acts of terrorism through the translation guidelines. The 2018 Al-Qur'an by the Ministry of Religion became one of the aspects that took part in overcoming all forms of acts of radicalism and terrorism after the government involved all elements of society and coincided with the publication of the 2018 edition of the Ministry of Religion's translation of the Qur'an.